(944) Social Insurance and Socioeconomic Development in UAR التأمين الاجتماعي والتنمية الاجتماعية والاقتصادية في الجمهورية العربية المتحدة - M. Fikry S. Gahin. (The Institute of National Planning, 2024)
Social insurance programs are basically designed to alleviate the financial burden of the loss of income and expense resulting from premature death, disability, sickness, unemployment and old age. Therefore, social insurance is primarily concerned with the economic well-being of the family unit in case any of the above unfortunate events happen to the breadwinner of that family and in public assistance programs the state offers financial help to needy families according to the merits of each case alone.